Impact of allergic rhinitis on quality of life and main risk factor: a study in Jazan region - Shamakhi, Radeif; Mubarki, Musleh (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2021)
Background: Allergic rhinitis is a common inflammatory disorder that affects the upper respiratory tract. It affects about one-third of the world’s population. The prevalence of rhinitis varies greatly in various countries and also in various parts of the same country. With this disease, the quality of life which includes sleep disturbances, fatigue, diminished memory, depression is decreased because of the direct impact on the life of the patient. Methods: The present cross-sectional study was conducted on patients over the age of 18 years old who suffered from symptoms of allergic rhinitis between 1 March 2021 to 30 March 2021 in Jizan region Patients were answered for questionnaires that sent for them online through social media. Results: A total of 37 participants enrolled. According to the ARIA guidelines, patients were divided into four groups: a moderate to severe intermittent group that comprised the majority of the patients 38%, a mild intermittent group 19%, a moderate to severe permanent group 27%, and a mild permanent group 15%. Among the total of 37 patients, the quality of life was mildly affected in 35% and severely influenced in 65% patients. Conclusions: In the patients studied in Saudi Arabia’s southern area, allergic rhinitis can have a negative impact on sleep quality, mood, and daily activities.